Thermodynamic and sustainability analysis of an organic rankine cycle system for turbofan engine - Mohd Nasir, Nur Athirah (2020)
With the advancement of aviation industry, the use of energy has increased and its environmental consequences have become more significant. The energy efficiency of the aircraft has been the major interest to restrain the energy consumption increment. Since the energy prices are rising worldwide, the idea of increasing energy efficiency is a continuous challenge for the industry. This is the reason why waste heat recovery (WHR) process is chosen to improve the energy efficiency of aircraft engine. By reusing this waste heat from the engine, the fuel consumption was reduced. Due to its unique features, Organic Rankine Cycle (ORC) is a powerful potential for this purpose. This thesis focused on the analysis of the Organic Rankine Cycle (ORC) from thermodynamics and sustainability aspects. The performance analysis was divided into two conditions of fluid which were subcritical and supercritical by including preheater or superheater. The new ORC system was then integrated to an aircraft turbofan engine. For a set of values of the initial parameters, the thermodynamic cycle of the system was solved in the MATLAB software to attain the net power output, thermal efficiency and the mass flow rate of working fluid. The integration of ORC to a turbofan engine was performed and the Thrust-Specific Fuel Consumption (TSFC) along with the fuel burn were evaluated. From the results, it was noted that a better fuel consumption could be accomplished by applying the ORC system to the turbofan engine with the aid of superheater at both subcritical and supercritical conditions which were noted as Case B and Case D. Taking into account the extra weight that can be added to the engine, the fuel burn reduction were 7.68% for Case B and 10.74% for Case D. The exergetic sustainability index has emerged to be a crucial method in determining the sustainability of a system. From this study, the two best cases, Case B and Case D demonstrated exceptional exergetic sustainability index at 0.474 and 0.470 respectively. The greater the value of sustainability index, the better it is for the practical applications. Both of the cases B and D showed a percentage improvement of 2.16% and 1.29% respectively compared to the turbofan engine without ORC system. By analyzing the thermodynamic performance and sustainability index of the system, this research indicated that ORC as waste heat recovery system is compatible and beneficial to the turbofan engine, as it improves the engine’s fuel consumption and overall performance.